Background Predictors and Event-Specific Characteristics of Sexual Aggression Incidents: The Roles of Alcohol and Other Factors. (August 2015) - Davis, Kelly Cue; Danube, Cinnamon L.; Stappenbeck, Cynthia A.; Norris, Jeanette; George, William H.
Sexual assault in the United States is an important public health concern. Using prospective longitudinal methods and responses from 217 community men, we examined whether background characteristics predicted subsequent sexual aggression (SA) perpetration during a 3-month follow-up period. We also examined event-specific characteristics of reported SA occurrences. Consistent with predictions, SA perpetration history, aggressive and impulsive personality traits, rape myth attitudes, and alcohol expectancies predicted SA (both non- and alcohol-involved) at follow-up. In addition, alcohol-involved assaults occurred more often with casual (vs. steady) partners but were more likely to involve condom use with casual (vs. steady) partners. Results suggest important avenues for future research and SA prevention efforts.